Peran Farid Husain dalam Perdamaian Aceh - Syah Putra, Rahmad (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
This study concerns the process of resolving the Aceh’s conflict and the role of one of the leaders in Aceh's peace, Farid Husain. The purpose of this study is to examine and to discuss the history of the resolution of the Aceh’s conflict, and the role of Farid Husain in Aceh peace In collecting the data, this study uses historical and descriptive analytical methods. The method of data collection is through three methods, namely observation, interview and documentation study. The results showed that during the conflict in Aceh, very much effort was made by the Government of the Republic of Indonesia to resolve the Aceh’s conflict, starting from the reigns of President Soekarno, Suharto, BJ, Habibie, Abdurrahman Wahid, Megawati Soekarno Putri, to President Susilo Bambang Yudhoyono's Government and Vice President M. Jusuf Kalla who became the solution to the peaceful conflict in Aceh through intensive direct dialogue between facilitated by the Crisis Management Initiative (CMI). Farid Husain was one of the people involved in the Aceh peace process who played a role in opening communication with GAM leaders and working behind the scenes to supply information about Aceh and GAM in the interests of the Indonesian peace team in resolving the Aceh conflict through peaceful means. The results of the study also found that the Aceh peace process was collectively carried out by various parties, not involving one actor, one of which was Farid Husain who played the role of To See The Actor, also involving various other figures including the Acehnese leaders themselves.